Draw chibi style : a beginner's step-by-step guide for drawing adorable minis : 62 lessons : basics, characters, special effects - Piuuvy (Quarry Books, 2023)
Draw Chibi Style teaches the essential techniques and adorable characters of this popular drawing style in 62 easy lessons.